Vegetation dynamics in response to climate change and human activities in the Hulun Lake basin from 1981 to 2019. (March 2022) - Gu, Yangyang; Pang, Bo; Qiao, Xuning; Xu, Delin; Li, Wenjing; Yan, Yan; Dou, Huashan; Ao, Wen; Wang, Wenlin; Zou, Changxin; Zhang, Xiaofei; Cao, Bingshuai
Highlights: We reconstructed the 39 years NDVI datasets to analyze vegetation dynamics and their responses to climate change and human activities. The vegetation coverage in the HLB presented a fluctuating trend due to the periodic warming and drying climate. The impact of human activities on vegetation greening or browning in the CGZ is greater than that in the MGZ. Abstract: Monitoring long-term vegetation dynamics is essential for developing adaptation strategy to address the challenges to the ecosystem posed by climate change and human activities. This study analyzed spatio-temporal changes of normalized difference vegetation index (NDVI) in the Hulun Lake Basin (HLB) from 1981 to 2019, and explored the relationship between climatic factors and NDVI datasets. Furthermore, the residual trend (RESTREND) method was used to distinguish between the impacts of changes in climate and human activities on vegetation dynamics. The results showed that NDVI of the basin initially increased to the 1990s, then decreased to the mid-2000s, and finally rebounded to 2019 owing to the periodic fluctuations in precipitation. There were 28.32% of the NDVI pixels significantly increasing and 13.85% of the pixels significantly decreasing. The increase proportion of vegetation coverage in forest, wetland and cultivated land was higher than other vegetation types. NDVI in the China Grass Zone (CGZ) significantly degraded by 20.39% compared with the Mongolia Grass Zone (MGZ) significantly degraded by 5.60%. NDVI was significantly correlated with precipitation and weakly correlated with temperature in the HLB, and precipitation was the principal factor influencing vegetation coverage. The results of RESTREND revealed that farmland reclamation, over-grazing, and open-pit mining led to greater browning of vegetation in the CGZ than in the MGZ. Meanwhile, the implementation of ecological protection and restoration projects have helped the greening of the vegetation in the CGZ (20.91%) compared with the MGZ (7.45%). China's ecological restoration projects are important for Mongolia to reverse the trend of serious ecological degradation. Our results can provide scientific decision-making for the local government to formulate differentiated vegetation ecological protection and restoration measures.